Civil engineers for the 1990s proceedings of the seventh Conference on Education and Training organized by the Institution of Civil Engineers and held at Kingston, Surrey, on 10-11 September 1985. (Thomas Telford, 1986)
A book aimed at those people involved in the training and education of graduate and post-graduate civil engineers. It deals with the best ways of education that meet the need for flexibility in consultancy and construction in civil engineering.